Constructivism in Qira'ah Learning for Arabic Language Development Students at UMM - Nasution, Annisa Hasanah; Wildana Wargadinata; Shofil Fikri (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
Reading skills play a crucial role as the basis for mastering other language skills, especially in understanding Arabic texts more deeply. Mastery of this skill allows students to interpret reading content, identify sentence structures, and enrich vocabulary. The application of constructivism theory in the learning process of reading skills at the Arabic Language Development Program of UMM supports the strengthening of students' understanding of reading skills, which is reflected in the improvement of their exam results. This research uses a qualitative approach and the method used is a case study. Then the data collection was done through observation, interview and documentation. The purpose of this study is to explain how the process of applying the theory of constructivism in learning reading skills in students of the Arabic Language Development Program at Muhammadiyah University of Malang. This research uses a qualitative approach and the method used is a case study. Then the data collection was done through observation, interview and documentation. After the data is collected, the data is analyzed by means of data reduction, data presentation and conclusion drawing. The results of this study indicate that the application of constructivism theory in learning reading skills in the Arabic Language Development Program.